BAREFOOT PLANTAR PRESSURE MEASUREMENT IN CHRONIC EXERTIONAL COMPARTMENT SYNDROME. Issue 22 (1st November 2016) - Roscoe, D; Roberts, A; Hulse, D; Hughes, M; Shaheen, A; Bennett, A
Abstract : Patients with chronic exertional compartment syndrome (CECS) have pain during exercise that usually subsides at rest. Accompanying the pain, a change in gait is frequently described by patients. This typically manifests as a progressive loss of control of ankle movements, often described as 'foot slap'. This study aimed to investigate the differences in plantar pressure between CECS cases and asymptomatic controls in a rested pre-symptomatic state. 20 men with symptoms of CECS of the anterior compartment and 20 asymptomatic controls participated. Barefoot plantar pressure was measured during walking and marching. Data was analysed to determine: stance time; foot progression angle; the mean of the medial-lateral displacement of centre of force; time from initial foot contact to initial full forefoot contact (IFFC-time); the medial-lateral distribution of pressure under the heel; and, the ratio between inner and outer metatarsal loading. Cases had shorter stance times and IFFC-times than controls. Foot progression angle was inversely related to walking speed. The area under the receiver operating curve for IFFC-time ranged from 0.746 −0.773 representing 'fair predictive validity'. Cases have an increased rate of ankle plantarflexion after heel strike. It has recently been observed that there is almost no change in the length of the tibialis anterior muscle during the gait cycle with almost all of the changes in length of the muscle-tendon unit occurring within the tendon during walking. It follows that lowering of the foot after heel strike occurs through tendon stretch whilst the muscle contracts isometrically. Therefore if IFFC is reduced in CECS cases it is plausible that this is due to stretching of the tendon although inherent weakness in the muscle cannot be excluded. This is postulated to result from either Tibialis Anterior muscle weakness or elongation of the tendon. The observed biomechanical difference in cases may give further insight into the pathophysiology of this condition and enable further development of a non-invasive diagnostic modality. Diagnostically, the value of IFFC-time is comparable to post-exercise invasive diagnostic tests but falls short of that achieved with invasive testing during prolonged painful exercise.